2023
DOI: 10.47604/jpid.1800
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of High Population on Economic Development of Pakistan

Abstract: Purpose: Population is an important factor which plays a double role in the economic development of Pakistan. From one side it is related to labor force. The larger size of the population has to produce more amount of the labor force. When resources are presented in sufficient amount, then labor force can become beneficial to economic development.  From the other side, the labor cannot produce anything alone, if resources are in scarce amount the afterwards larger workforce can become the obstacle to economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Bawazir et al (2021) They confirmed that the most important policy recommendation to the government is to position human capital development at the centre of its development strategy. Zahir (2023) revealed that the population is an important factor that plays a double role in the economic development of Pakistan. The larger size of the population produces a larger amount of the labour force.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bawazir et al (2021) They confirmed that the most important policy recommendation to the government is to position human capital development at the centre of its development strategy. Zahir (2023) revealed that the population is an important factor that plays a double role in the economic development of Pakistan. The larger size of the population produces a larger amount of the labour force.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, human capital could be understood as knowledge, skills, ability and experience of people to accomplish their jobs. Therefore, developing human capital involves increasing the skills and capabilities through investing in education and training (Akhtar, Renyong, Khaskheli, Ali, 2015). Other scholars conceptualised the term human capital as "the knowledge, skills competencies, and attributes embody in individuals that facilitate the creation of personal, social and economic well-being (Fugar, Ashiboe-Mensah & Adinyira, 2013: 466).…”
Section: Conceptualisation Of the Term Human Capitalmentioning
confidence: 99%
“…The theory focuses on the development of competences and skills of individuals for economic development (Akhtar et al, 2015). In this theory, individuals search for and maximise their economic interests.…”
Section: Origins and Overview Of The Theorymentioning
confidence: 99%